2020
DOI: 10.20956/zl.v1i3.11981
|View full text |Cite
|
Sign up to set email alerts
|

Desain Pelabuhan Wisata Untuk Menunjang Pariwisata Danau Toba

Abstract: Tempat pariwisata di Indonesia telah menjadi destinasi yang banyak dikunjungi bagi wisatawan dalam negeri maupun luar negeri. Danau Toba merupakan destinasi wisata prioritas, sehingga pariwisata ini sangat berpotensi untuk dikembangkan sebagai salah satu aset yang digunakan sebagai sumber yang menghasilkan bagi bangsa dan negara. Penelitian ini dilakukan untuk merencanakan desain pelabuhan wisata dan tata kelola pelabuhan di kawasan Danau Toba dengan tersedianya transportasi kapal ferry, kapal wisata, bus air.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The Thousand Islands is also a widely visited destination for domestic and foreign tourists and is included in the priority destinations in Indonesia. [1] Tourism is one of the main sources of income for this area, and therefore it is important to maintain a sustainable environment and natural resources. The development of a passenger port in Muara Angke is an important step in supporting the tourism sector in the Thousand Islands.…”
Section: Introductionmentioning
confidence: 99%
“…The Thousand Islands is also a widely visited destination for domestic and foreign tourists and is included in the priority destinations in Indonesia. [1] Tourism is one of the main sources of income for this area, and therefore it is important to maintain a sustainable environment and natural resources. The development of a passenger port in Muara Angke is an important step in supporting the tourism sector in the Thousand Islands.…”
Section: Introductionmentioning
confidence: 99%
“…An example is research related to the development of the Mandalika tourism destination that is planned as an area for the MotoGP event in October 2021 (Chotijah, 2021). Other examples are research related to brand perceptions equity in Borobudur Temple destinations in the XYZ generation (Pranatasari & Diva, 2020) and research related to developing tourist ports in the Lake Toba area (Azwar et al, 2020). It can be concluded that there has been no scientific research yet that discusses the resilience of Indonesia super-priority tourism destination in advance.…”
Section: Introductionmentioning
confidence: 99%